The impact of environmental dynamism on knowledge absorptive capacity-innovation performance relationship amongst manufacturing SMEs in Malaysia / Zarina Denan, Noraini Ismail and Noormala Amir Ishak - Denan, Zarina; Ismail, Noraini; Amir Ishak, Noormala (Research Management Institute (RMI), 2009)
This study examines the absorptive capacity construct at the organization level: its influence on the innovation performance. The primary question this study sought to answer was: How does absorptive capacity affect innovation performance? More specifically, the study examines the relationships of absorptive capacity dimensions and innovation performance. Also, the role of environmental dynamism, as a moderator on absorptive capacity-innovation performance relationship was also investigated. Absorptive capacity is defined as a firm's capability to complete the entire process from acquiring, disseminating and exploiting knowledge for commercial ends. This study focuses on three dimensions only; knowledge acquisition, knowledge dissemination and knowledge exploitation. The innovation performance concentrates on incremental innovation which includes product, service, method of production, market, sources of supply and ways of organizing. The study used a survey research method and regression analysis technique to examine the hypothesized relationships among constructs using data collected from 180 manufacturing SMEs in Malaysia. It was found that absorptive capacity is positively and significantly related to firms' innovation performance. Nevertheless, none of the dimensions of absorptive capacity was found significant. The environmental dynamism significantly moderates the relationship between absorptive capacity and innovation performance. The results indicated that both researchers and managers need to pay more attention on SMEs capability in acquiring, disseminating and exploiting knowledge and these capabilities must be integrated in order to achieve superior innovation performance. Also Malaysian SMEs are seen to be more absorptive in more stable environment which eventually enhances the innovation performance.